RETRACTED: A STEAM-Ethnoscience Approach to Coffee Plant Education - Abraham Akpertey; Kevin Piato; Purnama Sidik; Gandha Satria Adi (Ihsan Cahaya Pustaka, 2026)
RETRACTION NOTICE This article has been formally retracted by the Editorial Board due to confirmed authorship fraud. The listed lead author formally notified the journal that he did not author, contribute to, or approve the submission of this manuscript. Following preliminary verification, the Editorial Board determined that the submission involved unauthorized use of personal and academic identity, constituting a serious breach of publication ethics. The article has been retracted to preserve the integrity of the scholarly record. The original content has been removed from public access.